Empagliflozin Attenuates Neointima Formation After Arterial Injury and Inhibits Smooth Muscle Cell Proliferation and Migration by Suppressing Platelet‐Derived Growth Factor–Related Signaling - Gwo‐Jyh Chang; Wei‐Jan Chen; Yu‐Juei Hsu; Ying‐Hwa Chen (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2024)
Background Sodium–glucose cotransporter 2 (SGLT2) inhibitors reduce cardiovascular events. However, the precise mechanisms beyond glycemic control are not fully understood. The objective of this study was to determine the role of PDGF (platelet‐derived growth factor)–related signaling in empagliflozin‐mediated inhibition of neointima formation. Methods and Results Adult male nondiabetic Wistar rats were subjected to carotid artery balloon injury. Empagliflozin (30 mg/kg per day) was administered by oral gavage for 18 days beginning 4 days before surgery. The in vitro effects of empagliflozin on rat aortic vascular smooth muscle cell (VSMC) proliferation and migration were also determined. Empagliflozin attenuated balloon injury–induced neointima formation in carotid arteries. In VSMCs, empagliflozin attenuated PDGF‐BB‐induced proliferation and migration. Moreover, empagliflozin‐treated VSMCs did not undergo apoptosis or cytotoxic death. Empagliflozin suppressed PDGF‐related signaling, including phosphorylation of PDGF receptor β, Akt, and STAT3 (signal transducer and activator of transcription 3). Overactivation of PDGF signaling attenuated empagliflozin‐mediated inhibition of VSMC function. SGLT2 mRNA levels in rat VSMCs were undetectable, and SGLT2 silencing did not alter the empagliflozin‐mediated effects, supporting the SGLT2‐independent effects of empagliflozin on VSMC. Conclusions This study highlights the crucial role of suppressing PDGF‐related signaling in mediating the beneficial effects of empagliflozin on neointima formation and VSMC function, which are independent of SGLT2 and glycemic control. Our study provides a novel mechanistic aspect of empagliflozin for the prevention of vascular stenosis disorders.